Waiting for democracy: Political crisis and the discursive (re)invention of the 'national enemy' in times of 'Grecovery'. (July 2014) - Boukala, Salomi
This article seeks to identify the polarising rhetoric adopted by Greek mainstream political parties during the era of 'Grecovery'. The article focuses on the war of words between New Democracy, the leading party of the coalition government, and Syriza, the main opposition party on the occasion of the fourth anniversary of the murder of a 15-year-old schoolboy, Alexandros Grigoropoulos, by a police officer and the subsequent riots of December 2008 and the authorities' closure of the Hellenic Broadcasting Corporation (ERT). It draws on the political statements of two political parties – New Democracy and Syriza – and emphasises direct reference to the Greek civil war (1946–1949) and parallelisms of the current political climate with the colonels' dictatorship (1967–1974). In focusing on those obscure pages of Greek modern history, this article analyses the discursive construction of collective memories of two different political poles and examines how the Greek left and right wings legitimise and redefine their political identities through the prism of their divided past. Using the discursive strategies of the discourse historical approach (DHA), the article illustrates how the DHA can reveal silencing strategies that lead to the discursive construction of the distinction between 'Us' – 'democratic patriots' and 'Them' – 'enemies of the Greek nation'. Finally, recontextualisation in political rhetoric is highlighted as one of the ways of (re)constructing the tension and dichotomy between leftists and rightists. A systematic and explicit discourse analytic methodology of political rhetoric, that is based on history and (re)shapes collective memories, leads to an interdisciplinary approach that brings together and connects political rhetoric, argumentation and critical discourse analysis.